Evaluation of the Toxicity of Aconitum Heterophyllum (International Journal of Innovative Research in Computer Science & Technology, 2022)
Aconitum heterophyllum, commonly  known as aruna, belongs to the Ranunculaceae family and  is used in Ayurvedic formulations to treat diarrhoea, liver  difficulties, and other ailments. Alkaloids, proteins,  carbohydrates, saponins, amino acids, quinones,  flavonoids, glycosides, terpenoids, and other  phytochemicals are found in this plant. Not only are the  different medicinal characteristics of this plant mentioned  in this study, but the profile of its toxicological  experiments conducted on rats is also examined. Unlike  other Aconitum species, Aconitum heterophyllum was  proved to be helpful in a rat poisoning study. To begin, the  plant's ethanolic extract was tested for oral toxicity, but it  was found to be harmless. Castor oil's action was reversed  by an ethanolicextract of the plant. Furthermore, this plant  possesses antibacterial properties. After summarizing all  of this plant's medicinal characteristics, it might prove to  be a great source of information for academics, traditional  medicine practitioners, and the pharmaceutical business.
Keywords: Aconitum Heterophyllum; Anti Bacterial Role; Castor Oil; Phytomoleculs; Rats; Toxicity